Papers - Evaluation of Coal for Coke - Report of Committee on Evaluation of Coal for Blast-furnace Coke. - R. H. Sweetser (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1934)
The Committee on Evaluation of Coal for Blast-furnace Coke reports progress in the working out of the problem of evaluation. There has been no full meeting of the Committee but there have been several conferences with two or more of the members present, and the different members have expressed themselves freely on the five points that have been under consideration since the meeting of the Committee in New York on Feb. 16, 1932. The need of a method of coal evaluation, not only of coking coals but all other kinds, is obvious. Under NRA it becomes imperative that coals of the same size from the same seam be priced according to their variations in quality, especially in reference to cleanliness in respect to freedom from extraneous ash-forming materials. In looking over the correspondence that has passed between members of our Committee, it is evident that much of the confusion and misunderstanding would disappear if we could realize that practically all of the variations in value of coal from the same seam of coal are due to variations in the amounts of extraneous materials that are contained in the coal as it passes over the scales for shipment. It is not now a question with our committee as to the differentials in value, or in prices, between different kinds of coking coals or between noncoking and coking coals; our present problem is to arrive at the method for determining the scale of values of the coal from a certain coal seam according to the increase or decrease of extraneous ash and moisture from a predetermined base line adopted for that particular coal. The five points mentioned above are the same as discussed at the meeting in February, 1932, except that the temperature for determining the moisture content has been changed from 212" F. to 221" F., at the suggestion of Dr. A. C. Fieldner. The points are: 1. It is proposed that the coal industry adopt as a base line for evaluating all coals the analysis of the coal as it passes over the neighing device that determines the tonnage of coal bought and sold. 2. It is proposed that the Committee on Evaluation of Coal for Blast-furnace Coke approve the adoption of the base line for Pittsburgh seam coal presented by F. A. Jordan at the annual meeting of A.I.M.E.